The institutional dimension to urban governance and territorial management in the Lisbon metropolitan area - Crespo,José Luís (2010)
Approaches to governance have been influential in the design and implementation of urban policies. The state and public administration no longer play the exclusive role, focusing now on the coordination of interests for achieving collective goals. The organisational capacities of the central/regional and local powers are, therefore, critical to urban management efficiency. The article analyses the Lisbon metropolitan area, looking into practices of planning and governance in terms of (i) the role of municipalities determining patterns of development relative to the central state and public companies; (ii) the emergence of municipal and inter-municipal institutions and companies in the management and provision of services.